Enhancing customer brand love: The role of genuine personal branding and e-customer engagement - Bahri, Khoirun Nisa; Gaffar, Vanessa; Wibowo, Lili Adi; Dirgantari, Puspo Dewi (International Journal of Innovative Research and Scientific Studies, 2025)
Micro, small, and medium enterprises (MSMEs) play a vital role in supporting Indonesia’s economic growth. Enhancing customer satisfaction alone is not sufficient to maintain a competitive advantage due to the increasing level of competition in the Muslim fashion sector. Companies need to increase customer brand love to win the hearts of consumers. Therefore, this study investigates the related factors like Social Media Active Involvement (SMAI), Self-Brand Distinctiveness (SBD), Genuine Personal Branding (GPB) and E-Customer Engagement (ECE) to accommodate this intention. This study aims to determine the effect of SMAI and SBD on GPB simultaneously and partially. This research also aims to determine the influence of GPB on ECE, ECE on CBL, and GPB on CBL through ECE. Sampling was carried out using the purposive sampling method with 300 respondents. The research employed Covariance-Based Structural Equation Modeling (CB-SEM) for statistical analysis with hypothesis testing conducted using the AMOS software to evaluate causal relationships within the proposed structural model. After processing the data, the hypotheses were tested and discussed. This research indicated that SMAI and SBD had a significant combined influence on GPB. However, when considered individually, SBD did not have a significant effect on GPB. The results also showed that GPB significantly affected ECE, and ECE affected CBL. Furthermore, GPB mediated by ECE significantly affected CBL. Genuine personal branding is essential for MSMEs to increase e-customer engagement which ultimately also increases customer’s love for their brand as a practical implication.